Barriers to English Listening Comprehension for Indonesian University Students: Implications for Listening Curriculum Development - Sri Wahyuningsih; Revanda Putri Salsabila (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
English has been considered an important means of international communication not only for education but also for career advancement. In general, students find it difficult to understand expressions or sentences in English. The same thing occurs when learning listening comprehension for EFL students in Indonesia. Listening is one of the most difficult skills experienced by students in learning English. The research in this paper aims to investigate the barriers to English listening comprehension of university students in Indonesia and their implications for listening curriculum development. Data were garnered through semi-structured interviews with eight Indonesian higher-education students. The results depict that the barriers experienced by students in listening comprehension include a lack of pronunciation understanding and different accents, a lack of English vocabulary, a lack of voice clarity quality, and difficulty in understanding the speed of pronunciation. To improve listening comprehension, students need to practice listening to audio from native speakers repeatedly, English podcasts, speeches, and inspiring videos via YouTube, English songs, and watching movies. The implications for listening curriculum development were discussed in this paper.